Technique and Methodology for Objective Evaluation of Borrowings in Academic Texts - N. V. Avdeeva; E. N. Ivanova (Открытое образование (Москва), 2020)
Purpose. To provide a detailed justification of the methodological principles, guided by the specialists of the “Antiplagiat.RSL” project when conducting an independent assessment of the originality of scientific texts.Materials and methods. The implementation of these principles is demonstrated with the examples from the practice of tests. The proposed material based on more than ten years of experience of plagiarism – test practice, will give authors and administrators of scientific institutions a clearer idea of the procedure and requirements for academic texts.Results. The automated verification of academic texts for plagiarism has become commonplace, which affects all levels - from writing graduate qualification papers to defending doctoral dissertations, publishing monographs and textbooks. There is a wide range of software specially designed for comparing texts and identifying both distinct overlapping text fragments and paraphrased ones. At the same time, everyone who has come across the verification process understands that it is impossible to rely solely on the quantitative indicators presented in the system report. Evaluation of plagiarism-test results is an area where one has to deal with different, sometimes not entirely correct, understanding of the originality of scientific texts.The Russian State Library (RSL) is a national repository and, what is even more important - it remains independent from the academic institutional milieu. The article describes essential principles of the plagiarism tests, carried out at the RSL, which are based on the organizational legitimacy, identification of individual motivation and compliance with the actual normative regulation. Methodology of the tests founds on the five key principles: objectivity, confidentiality, consistency, specificity and complexity.In addition, certain issues of an objective evaluation of plagiarism are considered in order to draw attention to the fact that independent (delegated) verification of scientific texts is one of the components of the process of supporting academic integrity in modern conditions of dissemination and reproduction of information.Conclusion. A detailed check of the texts for plagiarism allows you to make corrections, modify the texts, and eliminate shortcomings caused by the author’s carelessness or negligence. At the same time, deliberate plagiarism even if it may seem insignificant, is the most serious misconduct from the point of view of scientific ethics, and institutional control in this area is necessary.